Boosting government reputation through CRM - da Silva, R.; Batista, L. (International Journal of Public Sector Management, 2007)
Purpose – The objective of this paper is to point out the potentialities of customer relationship management (CRM) in the building of government reputation by raising key aspects of corporate reputation theory that can be strengthened by similar CRM strategic orientations and supported by the deployment of CRM solutions. Design/methodology/approach – From a public sector perspective, the authors develop a comparative approach to corporate reputation and CRM premises, concepts, and practices. They draw aspects from both theories that can enable the building and management of corporate reputation in the public sector with the support of CRM solutions. Findings – Challenging the popular criticism that most public agencies and departments are bureaucratic, slow, and incapable of taking immediate action, governments are striving to revert this negative image by adopting new business approaches and applying new information technologies to optimize their processes. In this context, CRM has a potential value to fulfil government needs to become more responsive to the public. Practical implications – The considerations raised in this paper provide relevant issues for future research aimed at studying CRM and reputation in the government context. Public managers may benefit from the practical aspects and cases provided in this paper. Originality/value – A theoretical link is developed between CRM and corporate reputation, bringing a new dimension to the matter. Many public managers are leading projects to adopt customer?focused strategies without realizing they are also working on government reputation. An attempt is made to bring this awareness to the surface by linking some aspects of corporate reputation theory with CRM. Focusses on the public sector, which usually faces the problem of public cynicism.